Sociological studies of children and youth. Vol. 9 - Rosier, Katherine Brown (Amsterdam : London : JAI, 2003)
Two prominent themes of the volume are adolescents' transition to adulthood and children's time-use issues. Several chapters address each of these issues, including one examining children's labor in Senegal. Two ethnographic studies are included: one analyzes student-teacher interaction in an urban high-school math class, while the other examines friendship development and maintenance of early elementary-aged African American girls. The volume also includes a policy analysis of medical insurance provision for low income children, and a response to an earlier chapter on children's rights that appeared in Volume 8.
Introduction / K.B. Rosier -- Comment on Fine, Espeland, and Rojeck's "Young Citizens: the Position of Children in Communitarian Theory" / A. Etzioni -- Gender, race, class, and the transition to adulthood: a critical review of the literature / K.A. Mahaffy -- Neighborhoods and inequality: the possibilities for successful transition to adulthood / S. Bould -- Race/ethnicity, gender, and adolescents' occupational aspirations: an examination of family context / S.L. Blair et al. -- Child health, social policy, and the new chip program / J. Kronenfeld, K.M. Mathieson -- Children and housework: some unanswered questions / Yun-Suk Lee et al. -- Child labor and household survival strategies in West Africa / L. Bass -- Just play? A framework for analyzing children's time use / T. Chin, M. Phillips -- In girls, out girls, and always black: African-American girls' friendships / K.A. Scott -- Counterfeit classrooms: school life of inner-city children / S.H. Matthews.
Description based on print version record.
Keywords: Children; Age groups: children; Age groups: adolescents; Social Science -- Children's Studies